Al3+ ion intercalation pseudocapacitance study of W18O49 nanostructure - Thalji, Mohammad R.; Ali, Gomaa A. M.; Algarni, H.; Chong, Kwok Feng (Elsevier Ltd, 2019)
Intercalation pseudocapacitance is of essential significance for designing high performance electrode materials, which offers exceptional charge storage characteristics. In this study, we elucidate the pseudocapacitive behavior of Al3+ ions intercalation within the distinctive tunnels of monoclinic W18O49 nanostructure. 3D sea urchin-like W18O49 is synthesized through one-step solvothermal approach. Its physicochemical properties are investigated by X-ray diffraction, X-ray photoelectron spectroscopy, Field emission scanning electron microscopy and Brunauer-Emmett-Teller surface area analysis. Cyclic voltammetry, galvanostatic charge-discharge and electrochemical impedance spectroscopy techniques are used to investigate the electrochemical characteristics of W18O49 electrode in different electrolyte systems. It shows high specific capacitance of 350 F g−1 at 1 A g−1, superior electrochemical long-term stability in the Al3+ electrolyte with 92% capacitance retention at 8000 cycles. The excellent electrochemical performance is predominantly due to the Al3+ ions intercalation/de-intercalation with W18O49 nanostructure that is proven by ex situ X-ray diffraction analysis. The work marks a notable achievement in the effort of substituting commonly acidic proton electrolyte for W18O49 supercapacitor.